Pengaruh Aplikasi Kelas Bk (Bimbingan Konseling) terhadap Peningkatan Pengetahuan Remajatentang HIV-AIDS di Wilayah Kerja Puskesmas Talang Banjar Kota Jambi - Lismawati Lismawati; Septiwiyarsih Septiwiyarsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Based on World Health Organization (WHO), in 2011 there are 3,5 million people with HIV/AIDS in Southeast Asia. The trend of death caused by AIDS between 2001 and 2010 are different in every country side. In eastern Europe and central Asia, the number of people died from AIDS increased from 7.800 to 90.000, in Middle East and the North Africa increased from 22.000 to 35.000, in East Asia also increased from 24.000 to 56.000. According to WHO, 430.000 newborn child infected with HIV, in 2008, more than 90% infected by mother to child transmission. The purpose of this research is to determine the effect of the CG (Counseling guidance) class application to increasing in adolescent knowledge about HIV – AID. This research using pre experimental research design method with one group pretest posttest project,  this design used without using any control group and made the first observation (pretest)  which allows researchers to test the changes that occur on the experiment.  This study was conducted from 12 August – 12 September, with 30 respondent as a sample, the research data ware univariately and bivariately analysis through the t test with a = 0.05. The result of univariate analyzed shows 4.53 are the average pretest knowledge, while 11.87 are the average posttest knowledge, on the other way by bivariate analysis obtained 0.001 p-value, so it can be concluded that CG (Counseling guidance) class application affect on improving adolescent knowledge about HIV-AID in Puskesmas Talang Banjar before and after given CG class Application.Keyword: